Implementasi Model Problem Based Learning (PBL) pada Pembelajaran Keterampilan Menulis Teks Laporan Hasil Observasi untuk Meningkatkan Motivasi Belajar Siswa SMP - Yetisia, Meutia; Morelent, Yetty; Naini, Ineng (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This article explores the application of the Problem Based Learning (PBL) model in teaching junior high school students the skill of writing observation reports. Given the importance of writing skills and the challenges students face in terms of motivation, PBL is proposed as an effective solution for improving motivation and writing skills. This method emphasizes student engagement by presenting problems that are relevant to their lives, which can increase their motivation to learn. A quantitative study with a quasi-experimental design was conducted, involving two classes at SMPN 2 Sijunjung, to measure the impact of PBL on motivation and writing skills. The results showed that the implementation of PBL successfully increased student motivation, with 80% claiming to be more motivated after the program, and writing quality improved from an average score of 65 to 80. In addition, social interaction among students also increased, supporting collaboration in the learning process. Despite challenges in implementation, the results of this study demonstrate that PBL is a promising approach to improving motivation and writing skills in the classroom. Further research is needed to clarify the long-term impact of PBL in other learning contexts.